Cytokine mRNA profiles in trypanotolerant and trypanosusceptible cattle infected with the protozoan parasite trypanosoma congolense: Protective role for interleukin-4 - Mertens, B.; Taylor, K.; Muriuki, C.; Rocchi, M. (Mary Ann Liebert Inc, 1999)
African trypanosomes are important pathogens of both humans and livestock. We investigated the association of cytokine responses with disease susceptibility in Trypanosoma congolense-infected cattle. Changes in interleukin (IL)-1 beta, IL-2, IL-4, IL-5, IL-6, IL-12 p40, tumor necrosis factor-alpha (TFN-alpha) CD40L, and transforming growth factor-beta (TGF-beta) gene expression were compared in peripheral blood mononuclear cells of infected trypanotolerant N'Dama (Bos taurus) and trypanosusceptible Boran (Bos indicus) cattle. Results revealed that IL-2 transcription was decreased in both breeds of cattle at 21 days after infection. IL-12 p40 mRNA expression was increased in N'Dama cattle at 21 days after infection and at a later time in Boran cattle. The highest IL-4 mRNA expression was observed at 32 days after infection in N'Dama cattle. IL-6 mRNA expression increased in Boran cattle at 11 days after infection and was elevated at 21 and 32 days after infection in both breeds. Transcripts for IL-5 were barely detectable throughout the experimental period in both Boran and N'Dama cattle. Expression of TNF-alfa, IL-1 beta mRNA did not change notably during the course of infection. In summary, differences in the expression of IL-4 and IL-6 mRNA were identifed between the two breeds of cattle during infection with T. congolense, suggesting a possible protective role for IL-4 and a disease-promoting role for IL-6 in bovine trypanosomosis.